2018
DOI: 10.1002/ijc.31816
|View full text |Cite
|
Sign up to set email alerts
|

JMJD6 promotes hepatocellular carcinoma carcinogenesis by targeting CDK4

Abstract: Jumonji domain-containing protein 6 (JMJD6), a histone arginine demethylase, plays a multifaceted and significant role in embryonic development and cancer progression. However, the function of JMJD6 and its precise mechanism in regulating hepatocellular carcinoma (HCC) remain unknown. Here, we show that aberrant JMJD6 overexpression is associated with poor prognosis and aggressive characteristics of HCC. In hepatoma cell lines, we demonstrated that knockdown of JMJD6 inhibited hepatoma cell migration and proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 42 publications
0
55
0
Order By: Relevance
“…Cancer is a life-threatening malignancy that has become a global healthcare problem. [48][49][50] Using immunohistochemical methods, we recently reported that levels of crotonylation in eight types of cancer. 51 We found the expression level of crotonylation was down-regulated in liver, stomach and kidney carcinomas, and up-regulated in thyroid, oesophagus, colon, pancreas and lung carcinomas, suggesting that crotonylation may modulate different cancer progression.…”
Section: Regulation Of Cancermentioning
confidence: 99%
“…Cancer is a life-threatening malignancy that has become a global healthcare problem. [48][49][50] Using immunohistochemical methods, we recently reported that levels of crotonylation in eight types of cancer. 51 We found the expression level of crotonylation was down-regulated in liver, stomach and kidney carcinomas, and up-regulated in thyroid, oesophagus, colon, pancreas and lung carcinomas, suggesting that crotonylation may modulate different cancer progression.…”
Section: Regulation Of Cancermentioning
confidence: 99%
“…Aberrant CDK4 expression may result in increased proliferation, which is frequently observed in many types of cancer, including breast cancer, hepatocellular cancer and melanoma . JMJD6 promotes CDK4 expression by suppressing H4R3me 2(s) binding on the CDK4 promoter . Furthermore, JMJD6 interacts with p300/CBP‐associated factor (PCAF), a member of the GCN5‐related N‐acetyl transferase (GNAT) family of protein acetyltransferases, to regulate the histone modifications on the CDK4 promoter .…”
Section: Mechanisms Of Jmjd6 In Promoting Cancer Developmentmentioning
confidence: 99%
“…17 Overexpression of JMJD6 reduces the apoptosis of human hepatoma-derived cell lines. 17 The JMJD6 expression level is significantly increased in human hepatocellular carcinoma tissues than in normal liver tissues. 17 JMJD6 protein level in hepatocellular carcinoma is positively correlated with histological grade, and the JMJD6 mRNA level is significantly correlated with tumour grade and TNM stage.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
See 2 more Smart Citations